The environmental costs of the global digital economy in Asia and the urgent need for better policy. (November 2019) - Notley, Tanya
Digital services and products are often described as immaterial or virtual. However, they are responsible for a vast amount of environmental damage and destruction. The creation, processing, storage and movement of data relies on extensive natural and finite resources including electricity, water, metals, elements and chemicals as well as the production of human-made materials including plastics and glass; the disposal of these materials can produce toxic waste which is often illegally hidden and shipped around the world to bypass responsibility. Despite clear evidence of the materiality of digital flows, corporate rhetoric artfully acts to conceal the environmental risks and costs of digital flows, while state and international policy and regulation has thus far been unable to produce an effective response. This article seeks to examine the roots of this problem by reviewing the historical global policy discourse on the digital economy. The article is also grounded in Asia – which now accounts for almost half of the world's Internet users – by looking close up at State policies in the second most economically advanced country in the region: Singapore. The article concludes with a discussion of what needs to happen if states are to reduce the environmental burden of the digital economy and ensure the costs are more justly distributed.